Zero Waste Fashion Training: An Empowerment Strategy for the Women Learners “Cahaya Hati” Semarang - Musdalifah Musdalifah; Asih Kuswardinah; Dwi Putri Asih (Universitas Negeri Semarang, 2025)
This community service program aims to empower the women members of Rumpin Cahaya Hati in Pleburan Subdistrict, South Semarang District, Semarang City, through training in garment-making skills using zero-waste techniques. The program is motivated by the fact that most of the participants are unemployed, and therefore it is expected that they can make productive use of their free time while also developing sewing skills. The activity involved 15 participants and was conducted using training methods such as lectures, discussions, demonstrations, and hands-on practice. The program was carried out over four sessions, consisting of one theoretical session and three practical sessions. The outputs of the program included a garment-making module and women’s apparel products developed with a zero-waste approach. The training results indicated an improvement in participants’ knowledge and skills, covering body measurement, pattern making and modification, fabric cutting, sewing processes, and garment finishing with neatness and proper techniques. In addition, the outputs of the program were disseminated through publications in national journals, local mass media, and video highlights. This program is expected to create new economic opportunities for the participants, both for personal use and as a potential tailoring business in the future.